evaluate the expression for u = –3 and v = –4.

uv + u =

11 answers

To evaluate the expression \( uv + u \) for \( u = -3 \) and \( v = -4 \), we can substitute the values of \( u \) and \( v \) into the expression.

  1. First, calculate \( uv \): \[ uv = (-3)(-4) = 12 \]

  2. Next, calculate \( u \): \[ u = -3 \]

  3. Now, substitute these results into the expression \( uv + u \): \[ uv + u = 12 + (-3) = 12 - 3 = 9 \]

Thus, the final result is: \[ \boxed{9} \]

Evaluate the expression for v = –2 and w = –5.

vw =

To evaluate the expression \( vw \) for \( v = -2 \) and \( w = -5 \), we can substitute the values of \( v \) and \( w \) into the expression.

  1. Calculate \( vw \): \[ vw = (-2)(-5) = 10 \]

Thus, the final result is: \[ \boxed{10} \]

Evaluate the expression for n = –3 and p = –2.

np =

To evaluate the expression \( np \) for \( n = -3 \) and \( p = -2 \), we substitute the values of \( n \) and \( p \) into the expression.

  1. Calculate \( np \): \[ np = (-3)(-2) = 6 \]

Thus, the final result is: \[ \boxed{6} \]

Evaluate the expression for t = 11, u = –2, and v = 2.

tu 2 to the sec power + v =

To evaluate the expression \( tu^2 + v \) for \( t = 11 \), \( u = -2 \), and \( v = 2 \), we proceed with the following steps:

  1. Calculate \( u^2 \): \[ u^2 = (-2)^2 = 4 \]

  2. Now, calculate \( tu^2 \): \[ tu^2 = 11 \times 4 = 44 \]

  3. Finally, add \( v \) to \( tu^2 \): \[ tu^2 + v = 44 + 2 = 46 \]

Thus, the final result is: \[ \boxed{46} \]

Evaluate the expression for j = 9 and k = –5.

jk + j =

To evaluate the expression \( jk + j \) for \( j = 9 \) and \( k = -5 \), follow these steps:

  1. Calculate \( jk \): \[ jk = 9 \times (-5) = -45 \]

  2. Now, calculate \( jk + j \): \[ jk + j = -45 + 9 = -36 \]

Thus, the final result is: \[ \boxed{-36} \]

Evaluate the expression for r = 4 and s = 3.

rs 2 to sec power + r =

To evaluate the expression \( rs^2 + r \) for \( r = 4 \) and \( s = 3 \), we follow these steps:

  1. Calculate \( s^2 \): \[ s^2 = 3^2 = 9 \]

  2. Now calculate \( rs^2 \): \[ rs^2 = 4 \times 9 = 36 \]

  3. Finally, add \( r \) to \( rs^2 \): \[ rs^2 + r = 36 + 4 = 40 \]

Thus, the final result is: \[ \boxed{40} \]